Relationship of health behavior and academic performance among college students implications for University Health Service - Cleofas, Melvin Juan R.
Introduction: The effect on academic performance by students’ health behaviors have been shown by numerous studies. Health behaviors like sleep duration, intake of breakfast, smoking and alcohol use along with stress have shown varied results. This study described the health behaviors of college students and correlated them with their academic performance reflected in their grade weighted average (GWA). Implications on how to educate students about their overall health and promote a healthy university were derived from the results.